Intermittency in Wind‐Driven Surface Alteration on Mars Interpreted From Wind Streaks and Measurements by InSight. Issue 22 (20th November 2019) - Day, Mackenzie; Rebolledo, Laura
Abstract: Wind interacts with the surface of Mars to create the diverse landforms seen today. The morphology of wind streaks and related surface features has been used to interpret the winds on Mars in regions where actual wind measurement are lacking. Here we compare wind directions interpreted from bright wind streaks observed in orbitally‐acquired images with winds measured at the surface by the InSight lander in Elysium Planitia. The distribution of streak orientations is trimodal, dominantly reflecting winds from the southeast. The distribution of winds measured by InSight was highly variable with time of day but was dominantly characterized by winds from the northwest. The lack of coincidence between the two suggests that wind only intermittently deposits dust on the surface. The persistence of the streak orientations over five Mars years demonstrates that saltation in the region, if occurring, is not sustained long enough to rework these dust depositional surfaces. Plain Language Summary: Wind is responsible for much of the surface geology on Mars. Many previous works have used the surface geology to interpret wind directions in a given region with images taken from orbit. Here we compare winds interpreted from wind streaks seen in orbiter‐acquired images and winds measured by the InSight lander to see how well the two coincide. Over 120 Mars days, the directions interpreted from surface geology and measured at the surface did not match, suggesting that wind alters the Martian surface at some times more than other times. Key Points: Bright wind streaks in record winds dominantly from the southeast that do not coincide with winds measured by the InSight lander The interpreted and measured winds demonstrate that conditions only intermittently favor dust deposition on the surface Saltation has not been sustained for long enough in the region to rework and remove surface dust defining the streaks